DETERMINATION OF THE LIGHT CURVE OF THE ARTIFICIAL SATELLITE BY ITS ROTATION PATH AS PREPARATION TO THE INVERSE PROBLEM SOLUTION - Pavlenko, Daniil (Одеські астрономічні публікації, 2012)
Developing the algorithm of estimation of the rotational parameters of the artificial satellite by its light curve, we face the necessity to compute test light curves for various initially given types of rotation and specific features of lighting of the satellite. In the present study the algorithm of creation of such light curves with the simulation method and the obtained result are described.